Conflict-induced poverty: Evidence from Colombia (2014)
Colombia is a country with both high incidence of poverty and an ongoing civil conflict. This study uses measures of government deterrence and anti-narcotic activity as instruments of conflict-specific variables to estimate the impact of conflict on poverty in Colombia. Using census-level data at the municipality level for 2005, I assess the effect of conflict on both the urban and rural incidence of the newly developed Multidimensional Poverty Index. The findings show that the incidence of conflict significantly increases rural, but not urban, poverty. This is consistent with the fact that most of the conflict in Colombia takes place in rural areas. I also explore the lagged effect of conflict on poverty to conclude that it lasts for at least 3 years, but decreases over time. Finally, I show that the results are robust to a battery of additional specifications, including the use of alternative conflict data and a modified version of the dependent variable. © 2014 by Walter de Gruyter Berlin Boston 2014.